Integrating Tafsir Maqasidi into Environmental Preservation: A Study on Renewable Energy from Al Manar and At-Tahrir wa at-Tanwir Perspective - Qinta Berliana Valfini; Muhammad Ulinnuha (al-Afkar, Journal For Islamic Studies, 2026)
The survival of humankind is inseparable from the availability of adequate energy. At the same time, excessive exploitation of natural resources due to high dependence on fossil fuels has worsened environmental conditions and triggered various ecological problems that threaten the balance of the global ecosystem. Therefore, the transition to the use of renewable energy is crucial for achieving environmental sustainability. This study aims to examine the concept of environmental preservation through the perspective of tafsir maqasidi, by studying the tafsir al-Manar and at-Tahrir wa at-Tanwir in the context of energy sustainability. The research method used is descriptive-analytical, revealing how these two exegeses provide a foundation for sustainable energy policies within the framework of maqasid al-syari’ah. The findings show that the verses on preservation and renewable energy emphasize the importance of maintaining ecological balance, preventing damage, and utilizing sustainable natural resources. This study offers a new perspective on energy transition, viewing it as a technological innovation and a moral mandate that must be fulfilled by humanity to preserve the Earth for future generations.